2012
DOI: 10.1063/1.4766382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the surface charge screening and temperature on the vortex domain patterns of ferroelectric nanodots

Abstract: Based on the phase field simulations, effects of the surface charge screening and temperature on the vortex domain structure of the ferroelectric nanodot have been investigated. Our calculations show that the ferroelectric nanodot adopts a rhombohedral vortex domain pattern under an ideal open-circuit boundary condition. With the increase of the surface charge screening, the dipole vortex gradually rotates and appears rhombohedral-orthorhombic-tetragonal transformation. By adjusting the surface charge screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…For this domain pattern, the three components of the toroidal moment are almost equal with each other, i.e., | g x | ≈ | g y | ≈ | g z |. From the morphologies of equilibrium domain pattern in Figure 2a , we can see that this domain pattern actually has a single vortex with its toroidal axis along the <111> direction, in consistent with the prediction of a rhombohedral vortex domain pattern by previous works 27 33 . As the temperature further decreases, this rhombohedral vortex domain pattern keeps stable with its toroidal moment increasing gradually.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…For this domain pattern, the three components of the toroidal moment are almost equal with each other, i.e., | g x | ≈ | g y | ≈ | g z |. From the morphologies of equilibrium domain pattern in Figure 2a , we can see that this domain pattern actually has a single vortex with its toroidal axis along the <111> direction, in consistent with the prediction of a rhombohedral vortex domain pattern by previous works 27 33 . As the temperature further decreases, this rhombohedral vortex domain pattern keeps stable with its toroidal moment increasing gradually.…”
Section: Resultssupporting
confidence: 89%
“…It has been demonstrated that the domain structure in ferroelectrics could be dramatically changed by electric field, mechanical field and temperature, etc., which forms the base of domain and domain wall applications 6 7 19 31 32 33 34 35 36 . It would be much instructive for the application of VDS in ferroelectrics if the mechanisms of its formation and transformation are understood.…”
mentioning
confidence: 99%
“…Su et al [456] revealed the effect of intrinsic surface stress on vortex formation in ferroelectric nanoparticles. The screening charge effect on the domain structure in ferroelectric nanodots and short nanotubes has also been revealed [457][458][459][460]. Simulation results show that domain structures are highly dependent on the compensation of polarization-induced surface charges.…”
Section: Formation Of Ferroelectric Vorticesmentioning
confidence: 91%
“…With appropriately defining the order parameters and taking into account effects of electro-magnetro-mechanic fields, ambient temperature, and surface effects, PFS is also suitable to study multiferroic materials. Nevertheless, although PFS has been demonstrated its vitality in lots of ferroelectric materials [25][26][27][28][29], the development of PFS for multiferroic materials is still at the very beginning stage. To my best knowledge, a complete thermodynamic potential which incorporates both ferromagnetic order and ferroelectric order has not yet been reported for any single phase multiferroics.…”
Section: Methodsmentioning
confidence: 99%